2010
DOI: 10.2527/jas.2009-2412
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical assessment of apoptosis in different skeletal muscles of bulls during conditioning

Abstract: Apoptosis is a form of cell death that involves the changes of mitochondrial function and the regulated activation of caspase cascades, which selectively cleave cytoskeleton proteins and catalyze the changes of cell organelles and morphological structure. The changes of mitochondrial function, cell morphological structure, and degradation of cytoskeleton are considered to be responsible for the development of meat qualities. The LM, semitendinosus, and psoas minor (PM) muscles of 5 crossbred bulls were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 16 publications
7
36
0
Order By: Relevance
“…The caspase system has been shown to be involved in postmortem proteolysis and meat tenderization (HerreraMendez et al, 2006;Cao et al, 2010). However, the effect of added calcium chloride on caspase activities in muscle during postmortem conditioning needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…The caspase system has been shown to be involved in postmortem proteolysis and meat tenderization (HerreraMendez et al, 2006;Cao et al, 2010). However, the effect of added calcium chloride on caspase activities in muscle during postmortem conditioning needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…Kemp et al (2006b) detected caspase-3 (20 kDa) and caspase-8 (18 kDa) active fragments in the porcine muscles. Our previously published results indicated that there was a significant increase in caspase-3 activities and that apoptosis did exist in the bovine skeletal muscles during conditioning (Cao et al, 2010 and2013). Recently, in vitro proteolytic and chemical promoters treating experiments have shown that caspases were involved in postmortem proteolysis (Chen et al, 2011;.…”
Section: Introductionmentioning
confidence: 94%
“…Animals were humanely handled as described previously (Cao et al, 2010). Five crossbred bulls (Simmental × local Chinese yellow cattle in the Anhwei province) with ages from 22 to 24 months (body weight 443 ± 48 kg) were slaughtered in a local abattoir.…”
Section: Animals and Samplesmentioning
confidence: 99%
“…Moreover, sHSPs are chaperones that maintain cellular homeostasis and ultimately affect meat quality (Lomiwes et al, 2014). Therefore, a study has suggested that apoptosis and caspase activities can affect post-mortem meat quality (Cao et al, 2010). Apoptosis often occurs under specialized cellular conditions, such as cleavage of cytoskeletal proteins and cellular components, shrinkage of muscle cells, and loss of membrane asymmetry, which can lead to changes in meat quality (Sierra and Oliván, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies suggest that apoptosis during post-mortem conditioning is associated with meat quality (Cao et al, 2010). Small heat shock proteins (sHSPs) are well known anti-apoptotic molecules that regulate meat quality (Ouali et al, 2006).…”
Section: Introductionmentioning
confidence: 99%